Development of Biomass-Based Anion Exchanger for the Removal of Trace Concentration of Phosphate from Water - Poudel, Bhoj Raj; Aryal, Ram Lochan; Khadka, Lokjan Bahadur; Ghimire, Kedar Nath; Paudyal, Hari; Pokhrel, Megh Raj (Journal of Nepal Chemical Society, 2020)
Aluminum loaded saponified Mango Waste i.e. Al (III)–SMW adsorbent, which functions as anion exchanger, was developed by loading Al (III) onto lime treated Mango waste biomass. The characterization of adsorbent was done by an Energy Dispersive X-ray (EDX) spectroscopy and chemical analysis techniques. Elemental analysis showed an exchange of Ca (II) or K (I) from SMW with Al (III) during loading reaction via cation exchange mechanism. Phosphate adsorption is strongly pH-dependent and maximum adsorption occurs at pH around 7– 9. The maximum uptake capacity of Al (III)–SMW for phosphate was found to be 3.28 mg/g from the Langmuir isotherm model. The residual concentration of phosphate was sharply decreased by increasing the amount of Al (III)–SMW and reached less than 0.07 mg/L (from 9.7 mg/L) with the use of only 6 g/L of Al (III)–SMW whereas higher than 7 g/L successfully removed 100% of phosphate from water. The adsorbed phosphate was successfully desorbed and the adsorbent was regenerated using dilute alkali solution. Therefore, the Al (III)–SMW adsorbent investigated in this research work is expected to be a potential material for the treatment of water polluted with a trace amount of phosphate from aqueous solution.